İNŞACILIK ÇERÇEVESİNDE AVRUPA BİRLİĞİ'NİN İRAN NÜKLEER KRİZİNE YAKLAŞIMI - (:unkn) unknown (My University, 2015)
İranın nükleer programı, uluslararası alanda tartışmalara neden olmuştur. Avrupa Birliği (AB), İran nükleer krizi çözüm sürecinde aktif olarak yer almıştır. Birlik, İranın nükleer programına kuşkuyla yaklaş- mış ve İranın nükleer programını barışçıl sınırlarda tutmanın yollarını aramıştır. AB, İran nükleer krizinde diplomasi aracına ağırlık vermiştir. Bu kapsamda, İran ile çok sayıda görüşmeler yapılmıştır. Fakat görüş- meler tıkanma noktasına geldiğinde, İran dosyası Birleşmiş Milletler Güvenlik Konseyine (BMGK) gönderilerek krizde farklı bir evreye ge- çilmiştir. Bu dönemde de AB, diplomasi aracını etkili bir şekilde kullanmıştır. İnşacı kuram aracılığıyla ABnin İran nükleer krizine yönelik yaklaşımı yorumlanabilmektedir. İnşacı yaklaşım, aktörlerin kimlikleri temelinde dış dünyayı algıladıklarını ve araçlarını buna göre belirlediklerini ileri sürmüştür. AB de sahip olduğu kimliği temelinde krize diğer aktörlerden farklı yaklaşmıştır.

Iran s nuclear program has long been the subject of debate in the international arena. Here, the EU has been a particularly active participant in the process aimed at resolving the Iranian nuclear crisis, approaching Iran s nuclear program with suspicion while seeking ways to keep it within peaceful limits. To achieve this, the EU has employed a diplomatic focus, engaging in several rounds of negotiations with Iran. However, when negotiations ultimately reached a deadlock, the Iranian issue was brought to the United Nations Security Council (UNSC) and a different phase of the crisis came into being. During this period as well, the EU was able to effectively employ its means of diplomacy. Within this essay, the EU s approach to the Iranian nuclear crisis will be interpreted by way of constructivist theory, the core tenant of which contends that actors perceive the external world based on their identities and determine the best course of action according thereto. In this way, it will be argued that the EU has approached the Iranian nuclear crisis differently from other actors on the grounds of its identity.
THE EU S APPROACH TO THE IRANIAN NUCLEAR CRISIS WITHIN THE CONSTRUCTIVIST FRAMEWORK
Keywords: Nükleer Bilim ve Teknolojisi; Uluslararası İlişkiler